Design, analysis and fabrication of multipurpose kitchen utensils / Iman Qistina Abdul Razak and Suhadiyana Hanapi - Abdul Razak, Iman Qistina; Hanapi, Suhadiyana (School of Mechanical Engineering, 2022)
Nowadays, human life becomes more competitive and faster than previously. Automation brought about by technology has saved human effort and time to a large extent. Manual cutting and slicing of vegetables has proved to be very time consuming, use up lots of human energy, plus is a risky task in human busy life which could lead to unwanted accidents. This project idea aims to solve the issues by providing a unique product called Multipurpose Kitchen Utensils. The product is mainly designed to reduce time, human effort, and utensils during preparing cooking ingredients. Additionally, it can help to prevent accidental injuries plus make chopping and slicing cooking ingredients considerably easier and faster. Its features are fully automated utensils, can be used for multipurpose, changeable stainless steel sharp blade, easily portable, less power consumption, etc. The methodologies used to accomplish this task are product planning, customer needs identifying, product specification, concept designing, sketching designs, product engineering calculation and analysis, cost calculation for the product and fabrication detailing. Finally, the expected result of the study would assist and improve design and fabricate a mechanism that can help people to reduce time, human energy, and utensils during preparing cooking ingredients. Furthermore, it is expected to help prevent people from any unwanted accidents during preparing the cooking ingredients. Apart from that, the effectiveness and critical area of the mechanism design can be analysed. It is assumed that this project will provide 100% result based on target objectives and 80% benefits to end user, either home or professional